PENGEMBANGAN GENERAL KEY PERFORMANCE INDICATORS UNTUK PENINGKATAN KINERJA PLATO FOUNDATION - Putra, Rheza Dwi (Fakultas Ekonomi Universitas Wisnuwardhana, 2021)
ABSTRACT - This study aims to develop a checklist into a general KeyPerformance Indicator for improving the performance of the PlatoFoundation. The Performance Prism method is considered appropriate tobe used as an approach to measuring the performance of non-profitorganization stakeholders such as employees, donors, volunteers,organizational partners, and clients. The results of this study are a seriesof KPIs with a total of 45 KPIs based on the prism performance method.The 45 KPIs are divided into 5 Stakeholder Satisfaction KPIs, 5 StrategicKPIs, 5 Process KPIs, 5 Capability KPIs, and 5 Stakeholder ContributionKPIs for each stakeholder.Keywords: Key Performance Indicators, Performance Prism, PlatoFoundation